Chlorella vulgaris Supplementation Attenuates Lead Accumulation, Oxidative Stress, and Memory Impairment in Rats - Juan Pablo Diaz; Eduardo Pena; Samia El Alam; Cecilia Matte; Isaac Cortés; Leonardo Figueroa; Patricia Siques; Julio Brito (Toxics)
Lead is a harmful heavy metal known to alter the environment and affect human health. Several industries have contributed to the increase in lead contamination, making it a major global concern. Thus, remediation strategies are necessary to prevent lead bioaccumulation and deleterious health effects. The aim of this study was to determine the capacity of the green microalga Chlorella vulgaris (C. vulgaris or CV) to remove lead in an animal model and prevent the accumulation of this heavy metal in the principal organs (brain, liver, and kidney) and blood. Forty male Wistar rats were randomly assigned to four groups (n = 10): control group (CT); C. vulgaris supplementation group, 5% of the diet (CV); lead acetate administration group, 500 ppm (Pb); and C. vulgaris supplementation group, 5% of the diet plus lead acetate administration group, 500 ppm (CV–Pb). After 4 weeks of exposure, we measured lead accumulation, memory function, oxidative stress, and antioxidant activity (SOD and GSH). Lead exposure altered memory function, increased oxidative stress in the brain and kidney, and increased SOD activity in the brain. Supplementation with C. vulgaris restored memory function to control levels; reduced oxidative stress in the brain and kidney; and decreased the accumulation of lead in the liver, kidney, and blood of rats exposed to lead. Based on our results, C. vulgaris is a lead chelating and antioxidant agent in animal models.